2015
DOI: 10.1111/idh.12190
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive screening devices for oral lesions: their use by Canadian Dental Hygienists and the need for knowledge translation

Abstract: Current evidence and education through CE appears to bolster knowledge translation efforts for hygienists to become more comfortable in the use of ASDs. ASDs with minimal supporting evidence and not specifically targeted to hygienists, such as the brush biopsies, are not well utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(64 reference statements)
0
7
0
1
Order By: Relevance
“…Poor prognosis is primarily due to the late detection of OC. Several imaging devices and technologies can help clinicians visualise and describe oral potentially malignant diseases in real time at the point of care [ 36 , 37 , 38 ]. These devices can detect changes in optical properties (i.e., absorption, scattering and fluorescence), which are related to precancerous cancer and cancer development and progression in oral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognosis is primarily due to the late detection of OC. Several imaging devices and technologies can help clinicians visualise and describe oral potentially malignant diseases in real time at the point of care [ 36 , 37 , 38 ]. These devices can detect changes in optical properties (i.e., absorption, scattering and fluorescence), which are related to precancerous cancer and cancer development and progression in oral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding DHs conducting screening of oral lesions are few. Based on the answers from 369/3000 responders, an online email survey concluded that continuing education is needed for DHs to be able to be responsible for continuous surveillance of OPMDs 34 . To summarize, in advance of replacing tissue biopsies with brush biopsies for cytology, the recommendation is still to handle continuous surveillance of oral lesions at a specialist clinic, 50 which may explain the high propensity to refer patients to a specialist.…”
Section: Discussionmentioning
confidence: 99%
“…28 responders, an online email survey concluded that continuing education is needed for DHs to be able to be responsible for continuous surveillance of OPMDs. 34 To summarize, in advance of replacing tissue biopsies with brush biopsies for cytology, the recommendation is still to handle continuous surveillance of oral lesions at a specialist clinic, 50 which may explain the high propensity to refer patients to a specialist. The Swedish agency for health technology assessment and assessment of social services (SBU)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on the differential scattering of light by cellular components upon excitation with specific wavelength of light. SCC and highgrade dysplasia can be distinguished from normal tissue with high sensitivity with FV but less specific in identifying low-grade dysplasia [48]. Many molecules naturally present in the cells such as nicotinamide adenine dinucleotide (NADH), Flavin adenine dinucleotide (FAD), collagen, tryptophan, elastin, keratin, haemoglobin etc.…”
Section: Fluorescence Visualization (Fv)mentioning
confidence: 99%